AB0702 Capillaroscopic Findings in Patients with Suspected Primary Raynaud's Syndrome. (9th June 2015) - Moruno-Cruz, H.; Movasat, A.; Turriόn, A.; Ruiz, L.; Romero, M.L.; Perez, A.; Bohorquez, C.; Sanchez, A.; Cuende, E.; Albarrán, F.; Alvarez-Mon, M.
Abstract : Background: The presence of Raynaud's phenomenon involves the screening of connective pathologies. Because today capillaroscopy has become important as diagnostic criteria for scleroderma, within the protocol evaluation of patients with Raynaud it would be appropriate to hold at least one capillaroscopy, hence the interest of this study. Objectives: Descriptive study of capillaroscopic findings in patients with primary Raynaud's phenomenon suspected without other clinical data of connective pathologies. Methods: Capillaroscopic reports were reviewed of patients with positive Raynaud's phenomenon, positive or not antinuclear antibodies but negative ENA, who had no other data of connective pathologies, conducted between January 2012 and December 2014. Capillaroscopy was performed according to standard protocol, by a single physician experienced in capillaroscopy. Described three patterns: Normal pattern there may be some simple tortuosity. Suspicious pattern predominates capillary tortuosity in the form of spins and tangles. Scleroderma pattern: presence of giant capillaries, capillary bleeding and consequent destruction with avascular zones. Statistical analysis was performed using SPSS 15.0 software. Results: We found 69 patients who met the proposed criteria, of which 64 (93%) were women and only five (7%) male, the mean age was 39 years (±15.19). The history of snuff was present in 25 (36%) patients. Eight (12%) patients exposed to cold working. The ANA were positive in 18 (26%) patients, of these, 16 cases (89%) with ANA titers below 1/320; history of hypothyroidism was collected in 11 (16%) patients. The results of capillaroscopy no patient was seen sclerodermiform pattern being normal 65 (95.7%) patients, the dubious pattern was described only in 3 (4.3%) patients, with duration of more than 10 years in 2 cases and more 5 years in one case, three had positive ANA with a speckled pattern. Not was seen giant capillary or absence of capillaries in any patient, the tortuosity are described in 32 (46%) patients and in 4 (6%) patients was seen shoal-fish image. Conclusions: Our results agree with those reported in the literature on primary Raynaud's phenomenon is more common in women and in the absence of data connective pathologies (with the exception of positive ANA), hopefully a capillaroscopic normal result, further we help corroborate the primary origin of this disease. It is noteworthy that in patients with positive ANA most had titles below 1/320. the most common pattern capillaroscopic were simple tortuosity which could justify the structural pathophysiology of manifestation of the phenomenon of Primary Raynaud, these findings are consistent and that we know can be slight alterations as tortuous and irregular capillaries. We can conclude that the capillaroscopy is a useful tool in screening protocol of connective pathologies. We have yet to study the evolution of our patients over time, a normal capillaroscopy does not imply absence of autoimmune disease process and only prospective cohort studies will allow assess its real value. Disclosure of Interest: None declared